Time-resolved reflectivity technique: improvement and applications - K. M. A. EL-Kader (International Journal of Photoenergy)
A new method for determination of the reflectivity of Si in different phase transitions during pulsed laser irradiation is presented in this paper. This method is applied on TRR spectra of crystalline silicon (c-Si) in a medium of oxygen and amorphous hydrogenated silicon (a-Si: H). Time resolved reflectivity (TRR) measurements on silicon has been made during pulsed XeCl excimer laser irradiation (308 nm, 28nm FWHM) in a medium of oxygen. The samples were irradiated in the energy density range 400−100mJ/cm2. The reflectivity was measured with a probe He-Ne laser (632.8 nm). Depending on the energy density of the excimer pulse, heating, melting and resolidification of the surface were monitored by TRR spectra. From these measurements we were able to determine the melting threshold energy density for c-Si, depending on the energy densities, time of melting and maximum reflectivity have been measured. TRR spectra of a sample with 3μm thick a-Si layer for first shot of measurements were calibrated. A series of a-Si: H samples of the same thickness (0.34 μm) irradiated with a constant energy density 450mJ/cm2 and the three consecutive TRR spectra of the irradiated samples were calibrated.